2019
DOI: 10.1016/j.ajhg.2019.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Rare Variants in BNC2 Are Implicated in Autosomal-Dominant Congenital Lower Urinary-Tract Obstruction

Abstract: Congenital lower urinary-tract obstruction (LUTO) is caused by anatomical blockage of the bladder outflow tract or by functional impairment of urinary voiding. About three out of 10,000 pregnancies are affected. Although several monogenic causes of functional obstruction have been defined, it is unknown whether congenital LUTO caused by anatomical blockage has a monogenic cause. Exome sequencing in a family with four affected individuals with anatomical blockage of the urethra identified a rare nonsense varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 39 publications
0
50
0
1
Order By: Relevance
“…Human tissues, collected after maternal consent and ethical approval (REC 08/H0906/21 + 5), were provided by the MRC and Wellcome Trust Human Developmental Biology Resource 2 . Paraffin sections were processed for immunostaining after antigen retrieval, essentially as described ( Kolvenbach et al, 2019 ). Sections were probed with antibody to SLC20A1 (1:200; Proteintech 12423-1-AP).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human tissues, collected after maternal consent and ethical approval (REC 08/H0906/21 + 5), were provided by the MRC and Wellcome Trust Human Developmental Biology Resource 2 . Paraffin sections were processed for immunostaining after antigen retrieval, essentially as described ( Kolvenbach et al, 2019 ). Sections were probed with antibody to SLC20A1 (1:200; Proteintech 12423-1-AP).…”
Section: Methodsmentioning
confidence: 99%
“…Due to their ease of molecular manipulation and real-time observation, and the high fecundity of the species, we successfully used zebrafish larvae (zfl) to functionally characterize dominant variants reported in individuals with lower urinary tract obstruction (Kolvenbach et al, 2019). Here, we apply a similar zf model to investigate the role of slc20a1a in the zf urinary tract and urorectal development, and we combine this with human genomic, cell culture, and immunohistochemistry with regard to SLC20A1.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies (97, 98) have reported on a variety of copy number variants in patients with posterior urethral valves but a convincing pattern or stronger evidence of pathogenicity yet to emerge for these. Of note, a preliminary study reported multiple members over three generations affected by anatomical uretral obstruction who carried a heterozygous non-sense mutation of BNC2 (99). This gene codes for basonuclin 2 a zinc finger protein that is expressed in the embryonic urethra (99).…”
Section: Posterior Urethral Valvesmentioning
confidence: 99%
“…Of note, a preliminary study reported multiple members over three generations affected by anatomical uretral obstruction who carried a heterozygous non-sense mutation of BNC2 (99). This gene codes for basonuclin 2 a zinc finger protein that is expressed in the embryonic urethra (99). Furthermore, experimental downregulation of the homologous gene in zebrafish caused malformation of the distal part of the embryonic urinary tract (99), and mutant Bnc2 mice have malformed urethras (100).…”
Section: Posterior Urethral Valvesmentioning
confidence: 99%
See 1 more Smart Citation